Research on the Use of Artificial Intelligence as an Educational Methodology: Scientific Study with Social Listening and Scientometrics - Muñoz de Luna, Ángel Bartolomé; Martín Gómez, Sonia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The main objective of this research is to explore the development and implementation of Artificial Intelligence (AI) in the context of university education at a scientific and social level, through a systematic methodology of review academic articles and scientific papers (scientometrics) from the Web Of Science database for the scientific part and a social listening analysis of the main social networks for the social field. It is concluded that researchers should begin to analyze the effects of the good use of AI tools as a teaching methodology, so that society can also highlight it in it mentions on social networks.